ILC-based tracking control for linear systems with external disturbances via an SMC scheme - Yang, Rongni; Gong, Yingjie; Paszke, Wojciech (1975- )
Iterative Learning Control (ILC) is renowned for its capability to achieve precise tracking control for systems with repetitive actions at a fixed time interval. However, pursuing the dual objective of high-precision tracking and rapid convergence is a persistent challenge in the field of learning control. To address this problem, a novel ILC method is designed for a class of discrete-time linear systems subject to non-repetitive disturbances in this paper.
Keywords: iterative learning control (ILC) design; convergence; sliding mode control (SMC); non-repetitive disturbances